Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1139/cjce-2021-0078
|View full text |Cite
|
Sign up to set email alerts
|

Gradation characteristics-based interlayer mixture design method for enhanced rutting resistance of asphalt pavements

Abstract: The major role of interlayer mixtures is to mitigate reflective cracking by absorbing or dissipating concentrated stress, and relatively low-stiffness materials are typically used. However, there is a concern that interlayer mixtures may increase rutting potential due to the low-stiffness materials used. The dominant aggregate size range (DASR) porosity has been successfully applied for structural mixtures to ensure enhanced rutting performance. This study mainly focused on developing the new DASR porosity req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Pavement engineering scholars have found that the properties and gradation types of mineral aggregates can significantly affect the mechanical strength (resilient modulus and tensile strength) and engineering performances (permanent deformation, lowtemperature cracking, and moisture sensitivity) of hot mix asphalt mixtures (Sebaaly et al, 1997). Furthermore, it is beneficial to adjust the gradation composition of the aggregate to improve the performance of asphalt pavements while not changing the source and type of aggregate (Park et al, 2022). HMA mixtures are classified into five main categories based on gradation: stone matrix asphalt (SMA), stone asphalt concrete (SAC), large stone asphalt (LSA), superior performing asphalt pavements (Superpave), and conventional dense-graded asphalt concrete (AC) (Fang et al, 2019;Ferreira et al, 2020;Khasawneh and Alsheyab, 2020;Devulapalli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pavement engineering scholars have found that the properties and gradation types of mineral aggregates can significantly affect the mechanical strength (resilient modulus and tensile strength) and engineering performances (permanent deformation, lowtemperature cracking, and moisture sensitivity) of hot mix asphalt mixtures (Sebaaly et al, 1997). Furthermore, it is beneficial to adjust the gradation composition of the aggregate to improve the performance of asphalt pavements while not changing the source and type of aggregate (Park et al, 2022). HMA mixtures are classified into five main categories based on gradation: stone matrix asphalt (SMA), stone asphalt concrete (SAC), large stone asphalt (LSA), superior performing asphalt pavements (Superpave), and conventional dense-graded asphalt concrete (AC) (Fang et al, 2019;Ferreira et al, 2020;Khasawneh and Alsheyab, 2020;Devulapalli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have studied the influence of characteristics, gradation, and nominal maximum size of aggregate on the mechanical behavior and engineering performance of mixtures using methods based on different theories. Most findings indicated that the aggregate gradation has a significant impact on the resistance to rutting and permanent deformation of asphalt pavements (Kandhal and Mallick, 2001;Ferreira et al, 2020;Khasawneh and Alsheyab, 2020;Lira et al, 2021;Zhu et al, 2021;Devulapalli et al, 2022;Park et al, 2022).…”
Section: Introductionmentioning
confidence: 99%